Prevalence of depression, anxiety and burnout in medical students at the University of Namibia - Nelao T. Mhata; Vuyokazi Ntlantsana; Andrew Tomita; Kissah Mwambene; Shamima Saloojee (2023)
There is an increased prevalence of depression, anxiety, and burnout among medical students worldwide with no information from Namibia.This study aimed to determine the prevalence and factors associated with depression, anxiety, and burnout among medical students at the University of Namibia (UNAM).A quantitative descriptive cross-sectional survey was conducted utilising a specially designed questionnaire for the study and standardised instruments to evaluate depression, anxiety, and burnout.Of the 229 students in this study, 71.6% were female and 28.4% were male. The prevalence of depression, anxiety, and burnout was 43.6%, 30.6%, and 36.2%, respectively. The prevalence of emotional exhaustion (EX), cynicism (CY), and professional efficacy (EF) was 68.1% (n = 156), 77.3% (n = 177) and 53.3% (n = 122), respectively. In the final regression model, participants with a current psychiatric illness were more likely to screen positive for depression (adjusted odds ratio [aOR] 4.06, confidence interval [CI] 1.28-12.91; p = 0.02) and anxiety (aOR: 3.63, CI: 1.17-11.23; p = 0.03). Emotional exhaustion and cynicism were significantly associated with female gender (EX: aOR, 0.40, CI: 0.20-0.79; p = 0.01) (CY: aOR, 0.42, CI: 0.20-0.91; p = 0.03).More than one in three medical students at the UNAM were either depressed or burnt out.This is the first study to highlight the mental health needs of medical students at the University of Namibia.